Ulam-Hyers Stability and Well-posedness of the Fixed Point Problems for Contractive Multi-valued Operator in \(b\)-metric Spaces - Phiangsungnoen, Supak (Communications in Mathematics and Applications, 2016)
In this paper, we establish some fixed point results for new classes of contractive multivalued mappings via \(α_*\)-admissible mapping with respect to \(η\) in the class of \(b\)-metric spaces. To illustrate the obtained results, we provide some example. We also study the generalized Ulam-Hyers stability and well-posedness of fixed point problems are given. The theorems presented will extend, generalize or unify several statements currently exist in the literature on those topics.